What Is Ailing Africa? - Practical Philosophy in Reinventing Africa - Ouma, Stephen Onyango, (Africana Philosophy ;, 2024)
Not only does this book detail the colonial experiences in Africa through what the author refers to as a 'social construct,' it also vehemently criticises modern African governments for their current corruption and maintenance of the continent's situation. This book presents a two-pronged analysis of Africa's predicament by looking at the duality of ethics and identity. It tries to trace the problematic aspects of westernization and modernization within the contexts of neo-colonialism and continued exploitation of Africa by external forces, as well as the complicity of Africans themselves.